Ergosterol production at elevated temperatures by Upc2-overexpressing Kluyveromyces marxianus using Jerusalem artichoke tubers as feedstock. (October 2022) - Liu, Yanyan; Ren, Lili; Zhao, Junyi; Xia, Yitong; Zhang, Zhiyang; Guan, Xuyang; Huang, Sirui; Wang, Qiong; Wu, Jing; Yu, Zijun; Xu, Dayong; Li, Feng; et al.
Graphical abstract: Highlights: Overexpression Upc2 promoter ergosterol produce in K. marxianus (167.33 mg/L). 239.98 mg/L ergosterol was produced when glucose was replaced by fructose. Enhanced aeration improved ergosterol titer (128.46 or 100.28 mg/L) at 42 or 45 °C. 1124 or 948 mg/L ergosterol was obtained using JAT in bioreactor at 37 or 42 °C. Abstract: Ergosterol is an important precursor in the pharmaceutical industry for the production of numerous drugs. In this study, Kluyveromyces marxianus that showed more potential for ergosterol production than some other yeasts was reported. The effects of transcription factors UPC2, MOT3, and ROX1 of K. marxianus on ergosterol synthesis were explored, and a Upc2 -overexpressing strain produced 1.78 times more ergosterol (167.33 mg/L) than the wild-type strain (60.04 mg/L). A total of 239.98 mg/L ergosterol was produced when glucose was replaced with fructose to limit ethanol production. Enhanced aeration increased ergosterol titer from 63.09 mg/L to 128.46 mg/L at 42 °C. The ergosterol titer reached 304.37 mg/L in a shake flask at 37 °C, or 1124.38 and 948.32 mg/L at 37 °C and 42 °C, respectively, in a 5 L bioreactor, using Jerusalem artichoke tubers as the sole carbon source. This study establishes a platform for ergosterol biosynthesis using inexpensive materials.